2022
DOI: 10.1016/j.isci.2021.103628
|View full text |Cite
|
Sign up to set email alerts
|

Outer-coordination sphere in multi-H+/multi-e–molecular electrocatalysis

Abstract: Electrocatalysis is an indispensable technique for small-molecule transformations, which are essential for the sustainability of society. Electrocatalysis utilizes electricity as an energy source for chemical reactions. Hydrogen is considered the ''fuel for the future,'' and designing electrocatalysts for hydrogen production has thus become critical. Furthermore, fuel cells are promising energy solutions that require robust electrocatalysts for key fuel cell reactions such as the interconversion of oxygen to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 87 publications
(135 reference statements)
0
11
0
Order By: Relevance
“…This noncoordinated pyridine moiety could interact with protons present in intermediate species during the ORR and HPRR reactions. Proton shuttles in the second coordination sphere have led to a significant increase in turnover frequency (TOF) for many catalytic systems. , Given that no H + transfer is involved in the rate-determining step of the Cu-mediated ORR, we do not anticipate a significant effect on the catalytic rate here. , The third complex, [Cu­(fubmpa)­(H 2 O)­(OTf) 2 ] (Cu-fubmpa; fubmpa = N -(furan-2-ylmethyl)- N -[bis­(2-pyridyl)­methyl]­amine), was designed as an analogue of the copper complex [Cu­(bmpa)­(L)] 2+ (bmpa = bis­(2-pyridylmethyl)­amine), by introduction of the noncoordinating furanyl moiety while maintaining the nature of the central tertiary amine. We have selected these complexes because their E 1/2 values range between 0.2 and 0.5 V vs reversible hydrogen electrode (RHE), and, as far as we could observe, no limitations in electron transfer rates occurred within this selected series of tmpa modifications (see below), as opposed to our previous observations in the case of rigid terpyridine catalysts …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This noncoordinated pyridine moiety could interact with protons present in intermediate species during the ORR and HPRR reactions. Proton shuttles in the second coordination sphere have led to a significant increase in turnover frequency (TOF) for many catalytic systems. , Given that no H + transfer is involved in the rate-determining step of the Cu-mediated ORR, we do not anticipate a significant effect on the catalytic rate here. , The third complex, [Cu­(fubmpa)­(H 2 O)­(OTf) 2 ] (Cu-fubmpa; fubmpa = N -(furan-2-ylmethyl)- N -[bis­(2-pyridyl)­methyl]­amine), was designed as an analogue of the copper complex [Cu­(bmpa)­(L)] 2+ (bmpa = bis­(2-pyridylmethyl)­amine), by introduction of the noncoordinating furanyl moiety while maintaining the nature of the central tertiary amine. We have selected these complexes because their E 1/2 values range between 0.2 and 0.5 V vs reversible hydrogen electrode (RHE), and, as far as we could observe, no limitations in electron transfer rates occurred within this selected series of tmpa modifications (see below), as opposed to our previous observations in the case of rigid terpyridine catalysts …”
Section: Resultsmentioning
confidence: 99%
“…Proton shuttles in the second coordination sphere have led to a significant increase in turnover frequency (TOF) for many catalytic systems. 37,38 Given that no H + transfer is involved in the rate-determining step of the Cu-mediated ORR, we do not anticipate a significant effect on the catalytic rate here. 22,23 The third complex, [Cu(fubmpa (2-pyridyl)methyl]amine), was designed as an analogue of the copper complex [Cu(bmpa)-(L)] 2+ (bmpa = bis(2-pyridylmethyl)amine), 39 by introduction of the noncoordinating furanyl moiety while maintaining the nature of the central tertiary amine.…”
Section: ■ Introductionmentioning
confidence: 95%
“…Finding robust and efficient CO 2 RR catalysts has been of great interest, owing to their ability to mitigate atmospheric CO 2 . [9][10][11] However, most catalyst designs rely on transition metals. In 2010, Me ´nard and Stephen reported that CO 2 could be reduced to methanol (CH 3 OH) using an (Mes) 3 P(CO 2 )(AlX 3 ) 2 complex, where Mes is a mesitylene group and X is a bromide or chloride.…”
Section: Molecular Catalysts Bearing Main-group Elements At the Activ...mentioning
confidence: 99%
“…How-ever, while this approach has been successful for C 1 products, few examples exist to inform the design of electrocatalysts for C 2+ products. [48,52,53] One such example is the use of a molecular copper-porphyrin complex called copper(II)-5,10,15,20tetrakis(2,6-dihydroxyphenyl)porphyrin (PorCu), which orients functional groups toward the metal active site, resulting in excellent activity and selectivity for CO 2 RR to hydrocarbons in neutral aqueous media (Figure 3, example 1). [54] When operated at -0.976 V vs the reversible hydrogen electrode (RHE), PorCu catalyst exhibited a FE of ≈17% for ethylene production from CO 2 in a CO 2 -saturated potassium bicarbonate (KHCO 3 ) electrolyte, corresponding to a turnover frequency (TOF) of 1.8 molecules per site per second for ethylene, which is attributed to the reactivity of the Cu(I) metal center and the presence of built-in hydroxyl (OH) group in the porphyrin structure.…”
Section: Figurementioning
confidence: 99%